Thermal conductivity of MoS2 polycrystalline nanomembranes. (7th September 2016) - Sledzinska, M; Graczykowski, B; Placidi, M; Reig, D Saleta; Sachat, A El; Reparaz, J S; Alzina, F; Mortazavi, B; Quey, R; Colombo, L; Roche, S; Torres, C M Sotomayor
Abstract: Heat conduction in 2D materials can be effectively engineered by means of controlling nanoscale grain structure. A favorable thermal performance makes these structures excellent candidates for integrated heat management units. Here we show combined experimental and theoretical studies for MoS2 nanosheets in a nanoscale grain-size limit. We report thermal conductivity measurements on 5 nm thick polycrystalline MoS2 by means of 2-laser Raman thermometry. The free-standing, drum-like MoS2 nanomembranes were fabricated using a novel polymer- and residue-free, wet transfer, in which we took advantage of the difference in the surface energies between MoS2 and the growth substrate to transfer the CVD-grown nanosheets. The measurements revealed a strong reduction in the in-plane thermal conductivity down to about 0.73 ± 0.25 W m − 1 K − 1 . The results are discussed theoretically using finite elements method simulations for a polycrystalline film, and a scaling trend of the thermally conductivity with grain size is proposed.